Oedipus and the cabal: conspiracy theories and the decline of symbolic efficiency - Hughes, Brian (Frontiers in Communication, 2024)
Conspiracy theories are a means by which people make sense of vastly complex webs of cause and effect, contingency and random chance. The impersonal operations of political economy thus become personified in the figure of sinister puppet-masters controlling the world. Overdetermined historical events become narrativized as plots executed with clockwork timing and perfect secrecy. This paper proposes a model for the motives and mechanisms by which complex and ambiguous systems are made fodder for paranoid interpretation in the form of conspiracy theory. Using an exegetical close-reading methodology and psychoanalytic interpretive lens, it takes three meta-conspiracies as symptoms of the process described above: Antisemitic theories of globalization, the “Deep State” as seen from the political Left, and vulgar UFOlogy. This paper will argue that the impenetrable complexity of our globalized, financialized, hypermediated world agitates our experience of the Symbolic order, that is, the realm of language, logic, law, which acts as the scaffolding to the individual’s psychic sense of place in society. Lacan associates entry into the Symbolic order with the reconciliation of the Oedipal conflict and the Symbolic itself with the figure of the father. But the complexity and ambiguity of the Symbolic in our contemporary world produce a crisis in this dynamic, which some have described as a “decline in Symbolic efficiency.” This is particularly acute around events which give rise to conspiracy theories. The will of the father becomes unknowable, and the order upon which he insists appears dark and chaotic. Conspiracy therefore represents a turning away from this chaotic order, and a “dark return” to the pre-symbolic maternal, via the recession of the Symbolic into the Real, as a chaotic totalized presence (the conspiracy) stretching to occupy every corner of reality.